MODEL OF VILLAGE HEAD ELECTION ARRANGEMENT IN VILLAGE GOVERNANCE LAW - Sekar Anggun Gading Pinilih (Faculty of Law, Universitas Jenderal Soedirman, 2017)
This study aims to examine the right model in the arrangement of village head elections after the stipulation of Law No. 6 year 2014 on Village. This research is a normative law research by laws, historical, and conceptual approach. The result shows that a direct and simultaneous election model shall be the solution for the next Village Head Election. Simultaneous election model is designed since it is philosophically considered to make efficiency of the Village Head Elections, in terms of efficiency of budget, time and effort. The principle of this policy is an attempt to create a more equitable simultaneous democratization to minimize the chances of cheating. Since if the elections were not held simultaneously, it would give chance to the outsider to involve. The simultaneous election requires a coherent policy. This coherence will produce an effective synchronization of all types of elections implementation in Indonesia.Keywords: head of village, model, election, arrangement